The Effects of Sporting and Physical Practice on Visual and Kinesthetic Motor Imagery Vividness: A Comparative Study Between Athletic, Physically Active, and Exempted Adolescents - Dhouibi, Mohamed-Ali; Miladi, Imed; Racil, Ghazi; Hammoudi, Sabra; Coquart, Jeremy (Frontiers in Psychology, 2021)
The interest of motor imagery practice on performance and motor learning is well established. However, the impact of sporting and physical practice on motor imagery vividness is currently unclear, especially in youth. Two-hundred-and-forty adolescents were recruited to form different groups. For each age group (age-group 1, A-G1 with 13 years ≤ age ≤ 14 years 6 months vs age-group 2, A-G2 with 14 years 6 months < age ≤ 16 years), 40 athletes, 40 active adolescents and 40 exempted were recruited (20 girls and 20 boys in each category). Movement Imagery Questionnaire-Revised Second version (MIQ-Rs) was used to assess the Visual Motor Imagery (VMI) and Kinesthetic Motor Imagery (KMI) vividness. Results show that VMI is more evoked and more vivid than KMI (p < 0.001). Athletes had greater VMI and KMI than active and exempted groups (p < 0.001), and the active group also performed higher VMI and KMI than the exempted group (p < 0.001). Subjects from A-G2 had greater motor imagery than subjects from A-G1, and boys had better motor imagery than girls. Conclusion: the present results show that sport and physical education engagement is associated with enhanced motor imagery vividness, especially in VMI. Moreover, older adolescents evoke clearer images than younger adolescents, and boys have greater imagery ability than girls. Therefore, teachers and coaches should consider age and gender when developing this cognitive skill when learning, in physical education classes and sports clubs.